2016
DOI: 10.3390/nu8070433
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin AntiCancer Studies in Pancreatic Cancer

Abstract: Pancreatic cancer (PC) is one of the deadliest cancers worldwide. Surgical resection remains the only curative therapeutic treatment for this disease, although only the minority of patients can be resected due to late diagnosis. Systemic gemcitabine-based chemotherapy plus nab-paclitaxel are used as the gold-standard therapy for patients with advanced PC; although this treatment is associated with a better overall survival compared to the old treatment, many side effects and poor results are still present. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 89 publications
(152 reference statements)
1
77
0
Order By: Relevance
“…Curcumin has long been known to act as a therapeutic or preventive agent for the treatment of several major human cancers involved in a variety of antitumor cellular processes 28,29. It has been found that curcumin by oral administration had beneficial effects on several types of premalignant lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin has long been known to act as a therapeutic or preventive agent for the treatment of several major human cancers involved in a variety of antitumor cellular processes 28,29. It has been found that curcumin by oral administration had beneficial effects on several types of premalignant lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin, a diarylheptanoid compound, has shown to be effective against some types of cancer due to its antiproliferative effect caused by inhibiting angiogenesis and by inducing apoptosis, in vitro. 1 Also, curcumin was shown to have neuroprotective properties that may postpone or even prevent diseases as Alzheimer's, due ti its antiinflammatory and antioxidant properties. 2 Recent studies described the screening of Brazilian plant extracts for the antioxidant activity, as was made with six plant extracts aiming their antioxidant and photoprotective activity, which showed that the extract from Dalbergia monetaria is a potentially source of new antioxidants to be used in photoprotective formulations.…”
Section: Introductionmentioning
confidence: 99%
“…The administration of 8 g of curcumin orally had antitumor activity in this kind of patient [104,105]. However, the plasma curcumin levels remain low despite high administration doses.…”
Section: Therapies Against Oxidative Stressmentioning
confidence: 99%